N-Activated β-Lactams as Versatile Reagents for Acyl Carrier Protein Labeling - Prasad, Gitanjeli (Org Biomol Chem, 2012)
Acyl carrier proteins are critical components of fatty acid and polyketide biosynthesis. Their primary function is to shuttle intermediates between active sites via a covalently bound phosphopantetheine arm. Small molecules capable of acylating this prosthetic group will provide a simple and reversible means of introducing novel functionality onto carrier protein domains. A series of N-activated β-lactams are prepared to examine site-specific acylation of the phosphopantetheine-thiol. In general, β-lactams are found to be significantly more reactive than our previously studied β-lactones. Selectivity for the holo over apo-form of acyl carrier proteins is demonstrated indicating that only the phosphopantetheine-thiol is modified. Incorporation of an N-propargyloxycarbonyl group provides an alkyne handle for conjugation to fluorophores and affinity labels. The utility of these groups for mechanistic interrogation of a critical step in polyketide biosynthesis is examined through comparison to traditional probes. In all, we expect the probes described in this study to serve as valuable and versatile tools for mechanistic interrogation of fatty acid, polyketide, and nonribosomal peptide biosynthesis.